'An Immutably Personal Process': A Hospice Nurse Contemplates Uncontrol. (February 2016) - Duffy, Megen
Abstract : Updated several times a week with posts by a wide variety of authors, AJN 's blog Off the Charts allows us to provide more timely—and often more personal—perspectives on professional, policy, and clinical issues. Best of the Blog will be a regular column to bring AJN readers recent posts that we think deserve a wider audience. To read more, please visit:www.ajnoffthecharts.com .